Europe’s fragmented approach towards cyber security - Karine e Silva (Internet Policy Review, 2013)
The article proposes a deeper insight into the variety of concepts used to describe the term cyber security and the ways in which it has been used in recent years. It examines the role of three important actors involved in the internet governance arena, namely governments, private sector and civil society, and how they have influenced the debate. To this end, this paper analyses how different organisations, industry and societal actors see cyber security and how their interests influence the way the debate has evolved. The difficult balance between security and fundamental rights, although not new to governments and society, is of great importance for the internet. Citizens have engaged in favour of an open internet. However, little attention has been paid to the demands of citizens and how they may contribute to a concept of cyber security that brings society to its core. The paper states that for cyberspace to be open and supportive of innovation, the practice of cyber security needs to internalise the interests and perspectives of end users. A multistakeholder approach to cyber security asks a more participative environment where the rules of the game are decided with public participation and consultation, giving citizens the means and methods to influence the way cyber security is conceived and implemented. The paper concludes that although a citizen centric approach towards cyber security should be the way forward, this seems to be yet far from being included in the governmental agenda. The methodology applied in the paper was mainly focused on desk research.